2017
DOI: 10.20903/csnmbs.masa.2015.36.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Clay Improved Dispersion of Carbon Nanotubes in Different Solvents

Abstract: Hybrid nanofillers composed of different ratios of carbon nanotubes (CNTs) and sodium montmorillonite (MMT) were prepared by physically pulverizing both materials in powder form. Their dispersion behavior was investigated in different solvents (water, toluene and carbon tetrachloride). UV-vis spectroscopy showed that the absorbance at 550 nm for the CNTs becomes more intense with the increasing amount of added MMT, when water is used as a solvent, implying their improved dispersion. This is not so evident for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
3
0
0
Order By: Relevance
“…The bands from PEO are diminished in the Raman spectra of the samples containing the highest rGO concentrations, 10 and 20 wt%, because rGO at such high concentrations cannot be totally exfoliated, and the excess remains non-incorporated in the polymer matrix, thus resembling the spectral behavior of its initial, native compound. These considerations are agreeably explained by the manifestation of the D and G bands characteristic for the graphitic structure (G band at 1597 cm −1 , emerging from the C-C vibrations of delocalized p-electrons with sp 2 hybridization, and D band at 1335 cm −1 , distinctive for the defects in the graphitic structures with sp 3 hybridization [54,62]) that start to appear for the samples that contain 1 and 5 wt% rGO, alongside the bands characteristic for PEO. For higher rGO concentrations (10 and 20 wt%), as mentioned above, the spectral dominance features the rGO characteristic bands, D and G, completely suppressing the PEO bands (Figure 6, left panel).…”
Section: Resultssupporting
confidence: 66%
“…The bands from PEO are diminished in the Raman spectra of the samples containing the highest rGO concentrations, 10 and 20 wt%, because rGO at such high concentrations cannot be totally exfoliated, and the excess remains non-incorporated in the polymer matrix, thus resembling the spectral behavior of its initial, native compound. These considerations are agreeably explained by the manifestation of the D and G bands characteristic for the graphitic structure (G band at 1597 cm −1 , emerging from the C-C vibrations of delocalized p-electrons with sp 2 hybridization, and D band at 1335 cm −1 , distinctive for the defects in the graphitic structures with sp 3 hybridization [54,62]) that start to appear for the samples that contain 1 and 5 wt% rGO, alongside the bands characteristic for PEO. For higher rGO concentrations (10 and 20 wt%), as mentioned above, the spectral dominance features the rGO characteristic bands, D and G, completely suppressing the PEO bands (Figure 6, left panel).…”
Section: Resultssupporting
confidence: 66%
“…This suggested that, above a certain amount of EOMt in the matrix, a synergism engenders between EOMt and MWCNT, resulting in a sharp spin concentration decrease in the samples. The synergism between these two nanofillers was also reported in some previous works [16][17][18][19], manifested by their better dispersion in some solvents and polymer matrices, but this was for the first time demonstrated by changes in the ESR spectra of the MWCNT in dependence of the EOMt concentration in the nanocomposites.…”
Section: Introductionsupporting
confidence: 74%
“…17 Furthermore, the combination of these two nanofillers engenders synergism which results in their better dispersion. [18][19][20] This in turn enhances the mechanical properties of the rubber, something that was confirmed in recent publications. 21,22 Therefore in our study, 22 preceding this one, a series of natural rubber (NR)-based nanocomposites containing these two most exploited nanofillers, organomontmorillonite (OMt) which layers were further expanded for better dispersion (EOMt) and multiwall carbon nanotubes (MWCNT), were prepared.…”
Section: Introductionsupporting
confidence: 68%